From the Dutch corantos to Convergence Journalism: The Role of Translation in News Production - Valdeón, Roberto (Meta, 2012)
This article provides a overview of the role translation has played in news transmission since the birth of journalism until the 21st century. The paper focuses on three periods and the ways in which translation has been present in news production: (1) translation at the origin of newspapers in 17th- and 18th-century Europe, with particular reference to England, Spain and Scandinavia, where translation was, in fact, the staple diet of the first pamphlets published in those countries, (2) from the late 19th century onwards, the interplay between language and translation has also been present in the activity of foreign correspondents, albeit often in a very invisible manner, and (3) as the journalistic activity was professionalized, the importance of translation can be traced in the need for journalists to be trained in foreign languages as well as in the appearance of news agencies whose activity is to a great extent translational. Finally, the advent and spread of the Internet has made the role of translation more apparent, even if it remains an invisible second-rate activity within the news production process.